Ruthenium oxide based microelectrode arrays for in vitro and in vivo neural recording and stimulation. (1st January 2020) - Atmaramani, Rahul; Chakraborty, Bitan; Rihani, Rashed T.; Usoro, Joshua; Hammack, Audrey; Abbott, Justin; Nnoromele, Patrick; Black, Bryan J.; Pancrazio, Joseph J.; Cogan, Stuart F.
Abstract: We have characterized the in vitro and in vivo extracellular neural recording and stimulation properties of ruthenium oxide (RuOx) based microelectrodes. Cytotoxicity and functional neurotoxicity assays were carried out to confirm the in vitro biocompatibility of RuOx. Material extract assays, in accordance to ISO protocol "10993-5: Biological evaluation of medical devices", revealed no significant effect on neuronal cell viability or the functional activity of cortical networks. In vitro microelectrode arrays (MEAs), with indium tin oxide (ITO) sites modified with sputtered iridium oxide (IrOx) and RuOx in a single array, were developed for a direct comparison of electrochemical and recording performance of RuOx to ITO and IrOx deposited microelectrode sites. The impedance of the RuOx-coated electrodes measured by electrochemical impedance spectroscopy was notably lower than that of ITO electrodes, resulting in robust extracellular recordings from cortical networks in vitro . We found comparable signal-to-noise ratios (SNRs) for RuOx and IrOx, both significantly higher than the SNR for ITO. RuOx-based MEAs were also fabricated and implanted in the rat motor cortex to demonstrate manufacturability of the RuOx processing and acute recording capabilities in vivo . We observed single-unit extracellular action potentials with a SNR >22, representing a first step for neurophysiological recordings in vivo with RuOx based microelectrodes. Statement of significance: A critical challenge in neural interface technology is the development of microelectrodes that have recording and electrical stimulation capabilities suitable for bidirectional communication between the external electronic device and the nervous system. The present study explores the feasibility and functional capabilities of ruthenium oxide microelectrodes as a neural interface. Significant improvement in electrochemical properties and neuronal recordings are reported when compared to commercially available indium tin oxide and was similar to that of iridium oxide electrodes. The data demonstrate the potential for future development of chronic neural interfaces using ruthenium oxide based microelectrodes for recording and stimulation. Graphical abstract: Image, graphical abstract